Evaluation of Knowledge and Compliance of Nurses on The Use Personal Protective Equipment (PPE) in Intensive Care Unit (ICU) RSUD Panembahan Senopati Bantul Yogyakarta - Ayu Cahyaning Pramesti (Universitas Muhammadiyah Yogyakarta, 2017)
The purpose of this study is to evaluate the knowledge and compliance of nurses on the use of Personal Protective Equipment (PPE). This research use mix method research with descriptive survey approach and cross-sectional design. Quantitative data were obtained from distributing questionnaires with total sampling techniques. Qualitative data obtained from observation and interview. The results of this study found that as many as 12 people nurses (60%) have high knowledge and 8 people nurses (40%) have low knowledge. Besides that, it was found that 16 nurses (80%) were obeyed with the use of Personal Protective Equipment (APD) and 4 nurses (20%) were disobey in the use of Personal Protective Equipment (PPE). The conclusion of this research is nurses at Intensive Care Unit (ICU) of RSUD Panembahan Senopati Bantul have the high level of knowledge about Personal Protective Equipment (PPE) and they obey on the use of Personal Protective Equipment (PPE).